2018
DOI: 10.1021/acs.joc.8b02322
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Carbazoles: A Substituent-Governed Regioselectivity Profile

Abstract: Oxidative C−C coupling of carbazoles possessing various substituents is demonstrated in the presence of organic (metal-free) recyclable oxidants, such as DDQ or CA/H + , for accessing bicarbazole regioisomers. Differently substituted carbazoles are examined to showcase regioselective discrimination (3,3′-versus 1,3′-bicarbazoles) and preferences based on sterics and electronics in oxidative coupling. Finally, a mechanism that involves the carbazole radical cation has been traced (evidenced) and proposed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 101 publications
(81 reference statements)
3
34
0
2
Order By: Relevance
“…[30] and even more shiftedc ompared to that of [8]CPP (E onset ox = 0.93 V, HOMO = À5.33 eV). [41] This feature translates the more electron-rich character of [4]C-Et-Cbz.D espite the three molecules being constructed on the cyclic association of eight phenylu nits, the different first oxidation potential showst he importantr ole playedb yt he bridge (C versus N) on the electrochemical properties (and more precisely herein on the HOMO energy level).O ne can note that the trend is similart ot hat of their buildingu nits (HOMOs decrease from N-ethylcarbazole [42] to 9,9'-diethylfluorene [43] to biphenyl [44] ).…”
Section: Resultsmentioning
confidence: 95%
“…[30] and even more shiftedc ompared to that of [8]CPP (E onset ox = 0.93 V, HOMO = À5.33 eV). [41] This feature translates the more electron-rich character of [4]C-Et-Cbz.D espite the three molecules being constructed on the cyclic association of eight phenylu nits, the different first oxidation potential showst he importantr ole playedb yt he bridge (C versus N) on the electrochemical properties (and more precisely herein on the HOMO energy level).O ne can note that the trend is similart ot hat of their buildingu nits (HOMOs decrease from N-ethylcarbazole [42] to 9,9'-diethylfluorene [43] to biphenyl [44] ).…”
Section: Resultsmentioning
confidence: 95%
“…Recently,V enkatakrishnan and co-workers [33] found that, whereas carbazoles containing electron-donating groups form 3,3'-coupled products,s ubstrates bearing electron-withdrawing groups tend to form predominantly 1,1'-coupled molecules.T he dimerization of N-phenylcarbazole can also be achieved using Eatonsr eagent (composed of 7.5 wt % phosphorus pentoxide in methanesulfonic acid). [34] Thesynthesis of large graphenic structures from relatively simple molecules is usually not astraightforward task.…”
Section: Oxidative Homocoupling Of Arenes and Heteroarenesmentioning
confidence: 99%
“…Initial oxidation, mediated by DDQ, on the hydroxy termini of 5 forms the quinoidal species 9 . Alternatively, a one‐electron mechanism could also be a plausible pathway . Conjugate addition from the 2‐position of the furan positioned directly beneath the furan ring within the helicene framework gives oxocarbenium intermediate 10 , which tautomerizes to phenol 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Initial oxidation, mediated by DDQ,o nt he hydroxy termini of 5 forms the quinoidal species 9.Alternatively,aone-electron mechanism could also be ap lausible pathway. [26,27] Conjugate addition from the 2position of the furan positioned directly beneath the furan ring within the helicene framework gives oxocarbenium intermediate 10,w hich tautomerizes to phenol 11.I ts hould be noted that in the crystal structure of 10,the carbon atoms between which the bond is formed are placed directly above each other and are only 3.26 apart. Thenucleophilic phenol termini of 11 can then undergo intramolecular furan formation, which upon deprotonation, likely by the monoanionic hydroquinone of DDQ,forms the [9]circulene 8.…”
Section: Resultsmentioning
confidence: 99%